SOSIALISASI PENGENALAN KEUANGAN PERBANKAN SYARIAH PADA SISWA MTS AL-UTSMANI KAJEN - Aini Sarifatussaniyah; Naila Adiba; Assa'adatul Kamilah; Hendri Hermawan Adinugraha (Jurnal Pengabdian Masyarakat Kesosi, 2022)
Sharia banks have shown very rapid development, but there are still many people who have not understood Sharia banking, differences in sharia and conventional banks and what is sharia banking products. This service is done to help students better recognize the sharia banking finance in order to entrust them to save their money or invest their money to sharia banks or other sharia based financial institutions. They results show that is important to introduce sharia banking to increase the trust of sharia banks. This socialization is important as the form of introduction of sharia banking and entrusting the saving of funds in the sharia bank. Through this method of sosalization of students can easily understand banking sharia finances.